Arc-flash energy: The impact of fuse link manufacturers - Leite, Fabio Correa; Grimoni, Jose Aquiles B.; Malheiro, Fabio Mendes [UNESP]; Tomiyoshi, Luiz Kazunori (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The traditional operational and hazard control paradigm of an electrical installation has several issues pertaining to the diversity of equipment. A large maintenance inventory is a reason for concern for any manager, but the arc-flash hazard is a particularly new phenomenon, and the effects of equipment diversity on this phenomenon are even newer. The class of arc hazard can be simply increased by changing the fuse link or circuit breaker manufacturer. Management pressure to operate as well as nonstandard practices and installations are also partly responsible. The aim of this article is to take a typical situation in an industrial plant and to statistically simulate, by means of a dedicated software program, the fuse arc-flash interruption performance of various manufacturers. The purpose of this article is to obtain a more objective indication of the influence of different fuse link manufacturers on arc-flash incident energy. © 1975-2012 IEEE.
Keywords: Arc flash energies; Arc hazards; Arc-flash hazard; Electrical installations; Fuse-link; Hazard control; Incident energy; Interruption performance; Software program; Hazards; Industrial plants; Managers; Manufacture